Proteasome-associated cysteine deubiquitinases are molecular targets of environmental optical brightener compounds - Castro, Isel (J Cell Biochem, 2019)
The levels of organic pollutants, such as optical brightener (OB) compounds, in the global environment have been increasing in recent years. The toxicological effects and signal transduction systems associated with OB toxicity have not been thoroughly studied. The ubiquitin–proteasome system (UPS) plays a crucial role in regulating multiple essential cellular processes, and proteasome-associated cysteine deubiquitinases (DUBs), UCHL5 and USP14, are two major regulators for (de)ubiquitiation and stability of many important target proteins. Therefore, potential inhibition of UCHL5 and USP14 activities by some environmental chemicals might cause in vivo toxicity. In the current study we hypothesize that electrophilic OB compounds, such as DAST, FB-28 and FB-71, can interact with the catalytic triads (CYS, HIS, and ASP) of UCHL5 and USP14 and inhibit their enzymatic activities, leading to cell growth suppression. This hypothesis is supported by our findings presented in this study. Results from in silico computational docking and ubiquitin vinyl sulfone assay confirmed the UCHL5/USP14-inhibitory activities of these OB compounds that have potencies in an order of: FB71 > FB-28 > DAST. Furthermore, inhibition of these two proteasomal DUBs by OBs resulted in cell growth inhibition and apoptosis induction in two human breast cancer cell models. In addition, we found that OB-mediated DUB inhibition triggers a feedback reaction in which expression of UCHL5 and USP14 proteins is increased to compromise the suppressed activities. Our study suggests that these commonly used OB compounds may target and inhibit proteasomal cysteine DUBs, which should contribute to their toxicological effects in vivo.